Tietz fundamentals of clinical chemistry and molecular diagnostics - Tietz, Norbert W.; Rifai, Nader; Chiu, Rossa W. K.; Young, Ian; Wittwer, C. (St. Louis : Elsevier, 2024)
The Tietz Fundamentals of Clinical Chemistry and Molecular Diagnostics, 9th edition, edited by Nader Rifai, is a comprehensive, updated reference on laboratory science and clinical chemistry essential for clinical laboratory science (CLS) students and professionals. This edition builds on foundational topics of laboratory medicine, covering key areas like laboratory principles, analytical techniques, and instrumentation. Chapters also provide detailed discussions on analytes, pathophysiology, and molecular diagnostics, including the latest techniques in genetic testing and molecular biology. Each section is designed to improve diagnostic skills, emphasizing real-world applications through clinical cases, illustrations, and summary tables. *** This latest edition includes new updates to reflect emerging technologies, adds more review questions for reinforcement, and offers adaptive learning resources via Elsevier's Evolve platform. The textbook serves as a streamlined, practical guide that maintains depth while making complex topics accessible for students and practitioners alike.
PRINCIPLES OF LABORATORY MEDICINE -- 1. Clinical Chemistry and Molecular Diagnostics -- 2. Analytical and Clinical Evaluation of Methods -- 3. Preanalytical Variation -- 4. Biological Variation and Analytical Performance Specifications -- 5. Establishment and Use of Reference Intervals -- 6. Specimen Collection, Processing, and Other Preanalytical Variables -- 7. Quality Control of the Analytical Examination Process -- ANALYTICAL TECHNIQUES AND INSTRUMENTATION -- 8. Principles of Basic Techniques and Laboratory Safety -- 9. Optical Techniques -- 10. Electrochemistry and Chemical Sensors -- 11. Electrophoresis -- 12. Chromatography -- 13. Mass Spectrometry -- 14. Enzyme and Rate Analyses -- 15. Immunochemical Techniques -- 16. Automation in the Clinical Laboratory -- 17. Point-of-Care Testing -- ANALYTES -- 18. Amino Acids, Peptides, and Proteins -- 19. Serum Enzymes -- 20. Tumor Markers -- 21. Kidney Function Tests -- 22. Carbohydrates -- 23. Lipids and Lipoproteins -- 24. Electrolytes and Blood Gases -- 25. Hormones -- 26. Catecholamines and Serotonin -- 27. Vitamins and Trace Elements -- 28. Hemoglobin and Iron -- 29. Porphyrins and Porphyrias -- 30. Therapeutic Drug Monitoring -- 31. Clinical Toxicology -- 32. Toxic Elements -- PATHOPHYSIOLOGY -- 33. Diabetes Mellitus -- 34. Cardiac Function -- 35. Kidney Disease -- 36. Physiology and Disorders of Water, Electrolyte, and Acid-Base Metabolism -- 37. Liver Disease -- 38. Gastric, Intestinal, and Pancreatic Function -- 39. Bone and Mineral Metabolism -- 40. Disorders of the Pituitary Gland -- 41. Adrenal Cortex -- 42. Thyroid Disorders -- 43. Reproductive Endocrinology and Related Disorders -- 44. Pregnancy and Prenatal Testing -- 45. Newborn Screening and Inborn Errors of Metabolism -- 46. Pharmacogenetics -- MOLECULAR DIAGNOSTICS -- 47. Principles of Molecular Biology -- 48. Genomes, Variants, and Massively Paralleled Methods -- 49. Molecular Microbiology -- REFERENCE INFORMATION -- 50. Appendix: Reference Information for the Clinical Laboratory
Includes bibliographical references and index.
Keywords: Clinical chemistry; Molecular diagnosis; Chemistry, Clinical; Molecular diagnosis